Meta-Analysis: Effect of Hyperbaric Oxygen Therapy on Diabetic Foot Ulcer Recuperation - Faried, Faried Effendi Surono; Tamtomo, Didik Gunawan (Indonesian Journal of Medicine, 2024)
Background: Diabetes mellitus (DM) is a global phenomenon due to the high morbidity and mortality, especially in developing countries such as Indonesia. An ulcer is a wound and is usually found in patients who experience increased blood sugar and can cause peripheral blood vessel disorders, blood vessel disorders will result in peripheral neuropathy or a combination of both, diabetic ulcers are a condition often experienced by diabetes sufferers. Hyperbaric Oxygen Therapy (HBOT) is a therapy that is considered effective in healing diabetic ulcers and has been proven by many studies conducted. This study aims to analyze the effect of HBO therapy on the improvement of diabetic ulcer wounds. Subjects and Method: This was a systematic review and meta-analysis of primary studies. Article searches were carried out based on the PICO model. Population: diabetic ulcer patients. Intervention: Hyperbaric Oxygen Therapy. Comparison: placebo. Outcome: diabetic ulcers condition. Article searches were carried out from Google Scholar, MEDLINE/PubMed, Science Direct, Scopus, Hindawi, BMC, and Spinger Link databases. Keywords used "diabetic foot ulcers" AND "hyperbaric oxygen therapy". The inclusion criteria were full paper, RCT, and reporting risk ratio (RR). Selected studies were analyzed using the RevMan 5.3. Results: 9 RCTs from China, Canada, the Netherlands, Sweden, Egypt, Taiwan, England, and Turkey were selected for meta-analysis. HBO therapy increased diabetic ulcers condition (RR= 1.91; 95% CI= 1.17 to 3.12; p= 0.01). Conclusion: HBO therapy improves diabetic ulcers condition. Keywords: hyperbaric oxygen, diabetic foot ulcer, meta analisis.